2014
DOI: 10.1021/bi501141t
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Functional Characterization of Methicillin-ResistantStaphylococcus aureus’sClass IIb Fructose 1,6-Bisphosphate Aldolase

Abstract: Staphylococcus aureus is one of the most common nosocomial sources of soft-tissue and skin infections and has more recently become prevalent in the community setting as well. Since the use of penicillins to combat S. aureus infections in the 1940s, the bacterium has been notorious for developing resistances to antibiotics, such as methicillin-resistant Staphylococcus aureus (MRSA). With the persistence of MRSA as well as many other drug resistant bacteria and parasites, there is a growing need to focus on new … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 69 publications
(175 reference statements)
1
9
0
Order By: Relevance
“…The resultant conformer facilitates relocation of the Zn 2ϩ cofactor that advances the reaction by its stabilization of the nascent enediolate species. Our finding of a catalytic His residue on the mobile loop ␤6-␣8 reinforces recent efforts to inhibit class II aldolases by interference with this loop displacement (50,51). Furthermore, our proposed mechanism offers new insights into understanding substrate specificity and conformational states requisite for catalysis, critical knowledge in drug design, protein engineering, and more recently the synthesis of rare sugars (52).…”
Section: Tbp Inhibitionsupporting
confidence: 76%
“…The resultant conformer facilitates relocation of the Zn 2ϩ cofactor that advances the reaction by its stabilization of the nascent enediolate species. Our finding of a catalytic His residue on the mobile loop ␤6-␣8 reinforces recent efforts to inhibit class II aldolases by interference with this loop displacement (50,51). Furthermore, our proposed mechanism offers new insights into understanding substrate specificity and conformational states requisite for catalysis, critical knowledge in drug design, protein engineering, and more recently the synthesis of rare sugars (52).…”
Section: Tbp Inhibitionsupporting
confidence: 76%
“…Of the 11 positively selected proteins with known functions, two affect bacterial growth, i.e., phosphoribosylaminoimidazole-succinocarboxamide synthase purC which has been described to affect the growth of M. tuberculosis ( Brown et al, 2005 ) and Fructose-bisphosphate aldolase, frequently reported to be important for growth in pathogens such as M. tuberculosis and multidrug-resistant Staphylococcus aureus ( Capodagli et al, 2014 ; Puckett et al, 2014 ). The remaining nine proteins are associated with cell membrane entry (mce), transcription regulation (IclR family), reaction to heat shock (Hsp20), metabolic reactions ( trans- aconitate methyl transferase, 5-methyltetrahydropteroyltriglutamate–homocysteine methyltransferase), and probable endonuclease activity (as described for protein S16 in the 30S ribosomal subunit, by Oberto et al, 1996 ).…”
Section: Resultsmentioning
confidence: 99%
“…The decreased expression of mnhABCDEHF, specifically responsible for Na + /H + antiporter, suggested a decline of ΔΨ and energy biosynthesis (Castro et al 2016). The genes (nreB, ftnA, narGHT, nasD, pflAB, adh1, ldhAB, and natA) for energy metabolism were upregulated (1.3 to 7.8-fold), while trxAB (encoding thioredoxin and thioredoxin reductase) (Villanueva et al 2016), glpD (encoding glycerol-3phosphate dehydrogenase) (Szalus-Jordanow et al 2018), fda (encoding fructose-bisphosphate aldolase class 1) (Capodagli et al 2014), pgk (encoding phosphoglycerate kinase) (Liew et al 2015), and eno (encoding enolase) (Dai et al 2019) were downregulated. The results indicated that ID13 might negatively affect the endergonic processes such as ATP synthesis through mnhABCDEHF inhibition.…”
Section: Id13 Regulated S Aureus Cvcc 546 Gene Expressionmentioning
confidence: 99%